Investigations on the Performance of Metallic and Composite Body Armors. (2016) - Lakshmi, L.; Nandakumar, C.G.
Abstract: Body armor systems made of various materials and exhibiting distinct ballistic energy absorption mechanisms need to be considered for improving ballistic performance and energy absorbing mechanism of body armor. Modern armor materials such as composites and fabrics replace high density metals and alloys which hindered mobility and offered less protection. Armors are designed to prevent penetrating threats and internal damage that penetration will produce to human torso. The interaction between armor and human torso should be considered for actual performance of armor and for evaluating quality of protective effectiveness of armor against non-penetrating threats. Hence, linear elastic analysis of curved metallic and composite armors with continuum model and discrete model for the human surrogate target has been considered .